Why do wealthy parents have wealthy children? - Alexander Davenport; Peter Levell; David Sturrock (Institute for Fiscal Studies (IFS), 2021)
Why do the children of wealthy parents accumulate more wealth than children from poorer backgrounds? Does parental wealth have a role in determining young people's earnings, saving choices, returns to wealth and access to homeownership? How much wealth do parents give directly to their children? What other channels are involved in the persistence of wealth from one generation to the next? As wealth has grown compared with earnings, questions about the role of wealth in determining living standards and the transmission of wealth inequalities across generations have come to the fore. This report sheds light on why wealth inequalities persist across generations in the UK,using data that measure the wealth of parents and their adult children. We assess the role of education, earnings, saving decisions, portfolio decisions, access to homeownership and partners' earnings in transmitting inequalities in wealth across generations.
Keywords: 330; Vermögen; Vermögensverteilung; Intergenerationenmobilität; Generationengerechtigkeit; Eltern; Kinder; Großbritannien